2002
DOI: 10.1007/s00268-002-6621-0
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hyperparathyroidism Revisited in Menopausal Women with Serum Calcium in the Upper Normal Range at Population‐based Screening 8 Years Ago

Abstract: Population-based screening showed 2.1% prevalence of primary hyperparathyroidism (pHPT) in postmenopausal women. Individuals with total serum (s)-calcium levels of 2.55 mmol/L or more at screening were diagnosed with pHPT when subsequent analysis supported inappropriately elevated intact parathormone (PTH) levels in relation to even normal s-calcium levels. The arbitrary diagnostic criteria were validated by parathyroidectomy. Herein we reinvestigated biochemical signs of pHPT in women not diagnosed with pHPT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(62 citation statements)
references
References 28 publications
3
58
0
1
Order By: Relevance
“…PHPT is often a mild disease with a protracted course, asymptomatic in its early stages, with gradually rising calcium levels. The prevalence of clinical symptomatic pHPT in postmenopausal women has been estimated to be around 3% [34] and the prevalence of asymptomatic pHPT could be even higher. Whether this prevalence is high enough to affect calcium levels overall in this group might be questioned, but we think it is reasonable to assume a higher percentage of women with undiagnosed, asymptomatic pHPT in the higher serum calcium quartiles.…”
Section: Discussionmentioning
confidence: 99%
“…PHPT is often a mild disease with a protracted course, asymptomatic in its early stages, with gradually rising calcium levels. The prevalence of clinical symptomatic pHPT in postmenopausal women has been estimated to be around 3% [34] and the prevalence of asymptomatic pHPT could be even higher. Whether this prevalence is high enough to affect calcium levels overall in this group might be questioned, but we think it is reasonable to assume a higher percentage of women with undiagnosed, asymptomatic pHPT in the higher serum calcium quartiles.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in several studies secondary causes of PTH elevation have not been rigorously excluded. [15][16][17][18][19] Recently, Silverberg and Bilezikian have demonstrated that patients with NCHPT are at risk of disease progression, further developing features of classical hyperparathyroidism in certain cases, such as low bone mass, fragility fracture and kidney stones. Data also suggest that some of these patients will become hypercalcemic over time.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Lundgren et al 15 studied more than 5,000 postmenopausal women between the ages of 55 and 75 in a Swedish survey. They found that 16% of individuals had normal serum calcium levels (<9.9 mg/dL) and elevated PTH.…”
Section: Epidemiologymentioning
confidence: 99%
“…In the U.S., primary hyperparathyroidism (pHPT) has an incidence of approximately 100,000 patients annually with an overall prevalence of 0.2%-1% [1].The prevalence is higher in patients .65 years old (1.5%) [2] and is most common in postmenopausal women (2.1%-3.4%) [3]. pHPT is typically characterized by elevated serum calcium associated with inappropriately elevated parathyroid hormone (PTH) levels.…”
Section: Introductionmentioning
confidence: 99%